Characterisation of infection associated microRNA and protein cargo in extracellular vesicles of Theileria annulata infected leukocytes. (9th November 2018) - Gillan, Victoria; Simpson, Deborah M.; Kinnaird, Jane; Maitland, Kirsty; Shiels, Brian; Devaney, Eileen
Abstract: The protozoan parasites Theileria annulata and Theileria parva are unique amongst intracellular eukaryotic pathogens as they induce a transformation‐like phenotype in their bovine host cell. T. annulata causes tropical theileriosis, which is frequently fatal, with infected leukocytes becoming metastatic and forming foci in multiple organs resulting in destruction of the lymphoid system. Exosomes, a subset of extracellular vesicles (EV), are critical in metastatic progression in many cancers. Here, we characterised the cargo of EV from a control bovine lymphosarcoma cell line (BL20) and BL20 infected with T. annulata (TBL20) by comparative mass spectrometry and microRNA (miRNA) profiling (data available via ProteomeXchange, identifier PXD010713 and NCBI GEO, accession number GSE118456, respectively). Ingenuity pathway analysis that many infection‐associated proteins essential to migration and extracellular matrix digestion were upregulated in EV from TBL20 cells compared with BL20 controls. An altered repertoire of host miRNA, many with known roles in tumour and/or infection biology, was also observed. Focusing on the tumour suppressor miRNA, bta‐miR‐181a and bta‐miR‐181b, we identified putative messenger RNA targets and confirmed the interaction of bta‐miR181a with ICAM‐1. We propose that EV and their miRNA cargo play an important role in the manipulation of the host cell phenotype and the pathobiology of Theileria infection.